A Pilot Study On “A Study To Assess The Effectiveness Of Comprehensive Nursing Interventions (Hydrotherapy, Rice Heat Pad, Turmeric Therapy, Acupressure And Self Learning Booklet) On The Level Of Pain Perception And Dysmenorrhea Symptoms Among Adolescent Girls In Selected Settings At Chennai”. - J, Muneeswari; C, Susila.; ., Padmavathy (International Journal of Membrane Science and Technology, 2023)
Background: Menstruation is a natural phenomenon in women after puberty and is often associated with dysmenorrhea (Garg, 2015). Dysmenorrhea is very common, painful menstrual cramps of uterine origin, which is commonly divided into primary dysmenorrhea (pain without organic pathology) and secondary dysmenorrhea (pelvic pain with an identifiable pathologic condition, such as endometriosis or ovarian cysts) (Nagy, 2021). Doctors and other women give a lot of conflicting advice to reduce the pain during dysmenorrhea. To handle menstrual pain, we can utilize either the pharmacological or non-pharmacological methods. Pharmacologically, menstrual pain can be treated with medication. However, Non-pharmacologically, menstrual pain can be reduced by adequate rest, regular exercise (especially walking), water immersion, and pressing pressure points and by drinking traditional herbs such as turmeric water (Armour et al., 2019). Alleviation of pain during menstruation will result in good productivity and confidence among women. Aim of the study: To evaluate the effectiveness of comprehensive nursing interventions (Hydrotherapy, Rice heat pad, Turmeric therapy, Acupressure and Self-learning booklet) on pain perception and dysmenorrhea symptoms among adolescent girls. Methods and design: The study was conducted using a Quantitative approach with Quasi Experimental Time Series with 2 group pretest and posttest design. Forty-Eight adolescent girls in the age group of 13-17 years were selected by using random sampling technique for both experimental and control group. In phase I, Data about background variables was collected before pretest, using socio demographic Performa and menstrual Performa. The researcher has conducted pretest level of Dysmenorrheal symptoms were assessed during first menstrual cycle for the first three days (1st day, 2nd day, 3rd day) by using Numerical Rating scale (NRS) and modified menstrual symptoms questionnaire (MMSQ) to the control group and experimental group. Comprehensive Nursing Interventions ((Hydrotherapy, Rice heat pad, Turmeric therapy, Acupressure and Self-learning booklet) were given to adolescent girls in experimental group on individual basis. Assessment of Effectiveness of Comprehensive Nursing Interventions on level of pain perception and dysmenorrheal symptoms were measured by using same pretest scale. The major findings of the study: Comprehensive Nursing Interventions ((Hydrotherapy, Rice heat pad, Turmeric therapy, Acupressure and Self-learning booklet) is an intervention in reducing Pain perception and dysmenorrheal symptoms as the pre-test mean score, SD and Mean percentage of experimental group shows that Mean (7.42±1.8) and control group Mean (7 ±2.34) on level of pain perception among adolescents with dysmenorrhea. So, the difference is 0.42, not statistically significant. Pretest mean score, SD, and Mean percentage of dysmenorrheal symptoms in experimental group shows that Mean (127.38±8.88) and control group Mean (125.25± 7.66) among adolescents with dysmenorrhea. So, the difference is 2.13, not statistically significant, assessed using student independent t-test. In posttest, there was a significant difference between experimental and control group of adolescent girls. The significant p- values 0.001 indicates, the level of pain perception and dysmenorrheal symptoms score were not similar in both groups, calculated using chi square test. Experimental groups are reduced the 44.20% of pain perception score and 20.67% of dysmenorrheal symptoms score after having comprehensive nursing interventions and control group are reduced only 2.90% of pain perception score and 1.61% of dysmenorrheal symptoms after routine care. There is significant association between posttest level of pain perception and demographic variables of adolescent girls with the age group of 13-14 years and 10th standard and posttest level of pain perception and menstrual variables of adolescent girls with 28 days menstrual cycle and moderate extent of blood loss in experimental group. There is significant association between posttest level of dysmenorrheal symptoms and demographic variables of adolescent girls with the type of family and family history and posttest level of pain perception and menstrual variables of adolescent girls with day of flow and material used in experimental group. Discussion: The findings of the study enlighten the fact that comprehensive nursing interventions can be used as cost-effective interventions and showed higher participant satisfaction during intervention by reducing the level of pain perception and dysmenorrheal symptoms score in adolescent girls with primary dysmenorrhea.